PENERAPAN STRATEGI PEMBELAJARAN PARADIGMA PEDAGOGI IGNATIAN (REFLEKTIF) TERHADAP PENINGKATAN HASIL BELAJAR DAN MOTIVASI BERPRESTASI BELAJAR ILMU PENGETAHUAN ALAM (IPA) SISWA KELAS V SEKOLAH DASAR - Albertus Hartana; Punaji Setyosari; Dedi Kuswandi (Graduate School of Universitas Negeri Malang, 2016)
The Ignatian Pedagogy Paradigm is an art of thinking and doing something thoughtfully that incorporate humanistic values into learning subjects consciously. This paradigm endorses meaning of each topic within in learning materials based on students’ own experience. Students take into their consciousness life values (Reflective Moment) withlearning materials by themselves or by their groups in order that they can practice it in daily life (Action). Researcher elaborates action research method for resolving learning problems within Fifth Grade (second group) of Kanisius Elementary School Students of Sengkan Yogyakarta during natural sciences class. Researcher implements Ignatian Pedagogy Paradigm within the method. The research follows the guidance prepared by Bruce W. Tuckman and Brian E. Happer (2012). First cycle shows that mean value is 13,85 for students learning outcomes. Second cycle shows that mean value is 15,03 for students learning outcomes. The average difference between the first cycle and the second is 1,175. It says that learning outcomes of the first cycle is lower than the second; and of the second cycle is higher than the first. Value of “t” Test by counting is 2,466; and Value of “t” Test according to the statistic table is 2,000 with 0,016 score of probability and by 0,05 significant level. The research shows that the value of “t” Test by counting is higher than value of “t” Test according the statistic table. It means that implementation Ignatian Pedagogy in natural sciences subject improves study results of Fifth Grade (Second Group) of Kanisius Elementary School Students of Sengkan Yogyakarta. First cycle shows that mean value is 108,23 for students learning motivation. Second cycle shows that mean value is 116,05 for students learning motivation. The value difference between the first and the second is 7,825. It says that learning motivation of the first cycle is lower than the second; and of the second cycle is higher than the first. Value of “t” Test by counting is 2,572; and Value of “t” Test according to the statistic table is 2,000 with 0,012 score of probability and by 0,05 significant level. The research shows that the value of “t” Test by counting is higher than value of “t” Test according the statistic table. It means that the implementation of Ignatian Pedagogy in natural sciences subject improves learning motivation of Fifth Grade (Second Group) of Kanisius Elementary School Students of Sengkan Yogyakarta.Paradigma Pedagogi Ignatian (Reflektif) adalah cara berpikir dan bertindak yang menyaturagakan nilai-nilai kemanusiaan ke dalam setiap materi ajar. Para siswa tidak hanya difasilitasi mengetahui materi ajar saja, tetapi juga untuk menemukan makna dan nilai-nilai yang terkandung dalam setiap materi ajar. Para siswa aktif mencari sendiri dan atau bersama-sama dengan teman sebaya, nilai-nilai kemanusiaan dari setiap materi ajar (refleksi) dan mewujudnyatakan nilai-nilai tersebut dalam tindakan nyata (aksi). Dalam penelitian ini, peneliti menggunakan Penelitian Tindakan Kelas (PTK), untuk membantu memecahkan permasalahan yang terjadi di kelas VB Sekolah Dasar Kanisius Sengkan Yogyakarta, dalam proses pembelajaran IPA dengan pembelajaran Paradigma Pedagogi Ignatian (Reflektif). Peneliti mengadopsi model PTK yang dirancang oleh Bruce W. Tuckman and Brian E. Happer (2012). Nilai rata-rata hasil belajar siklus 1 adalah 13,85 dan siklus 2 adalah sebesar 15,03 dengan demikian diperoleh perbedaan rata-rata sebesar 1,175 dimana nilai rata-rata hasil belajar siklus 1 adalah lebih rendah dan hasil belajar siklus 2 adalah lebih tinggi. Dari uji t diperoleh nilai t hitung sebesar 2,466 dan t tabel sebesar 2,000 dengan probabilitas sebesar 0,016 pada taraf signifikansi 0,05. Karena nilai t hitung lebih besar dari tabel dan karena probabilitasnya jauh di bawah 0,05, maka penerapan pembelajaran Paradigma Pedagogi Ignatian (reflektif) dapat meningkatkan hasil belajar siswa kelas VB SD Kanisius Sengkan Yogyakarta, dalam pembelajaran IPA. Hasil penelitian tentang motivasi berprestasi siswa diperoleh bahwa nilai rata-rata motivasi berprestasi siklus 1 adalah 108,23 dan siklus 2 adalah sebesar 116,05, dengan demikian diperoleh perbedaan rata-rata sebesar 7,825 dimana nilai rata-rata motivasi berprestasi siklus 1 adalah lebih rendah dan nilai rata-rata motivasi berprestasi siklus 2 adalah lebih tinggi. Dari uji t diperoleh nilai t hitung sebesar 2,572 dan t tabel sebesar 2,000 dengan probabilitas sebesar 0,012 pada taraf signifikansi 0,05. Karena nilai t hitung lebih besar dari tabel dan karena probabilitasnya jauh di bawah 0,05, maka penerapan pembelajaran Paradigma Pedagogi Ignatian (Reflektif) juga dapat meningkatkan motivasi berprestasi belajar siswa kelas VB SD Kanisius Sengkan, Yogyakarta dalam pembelajaran IPA.